SURGICAL TREATMENT OF THE PROXIMAL HUMERUS FRACTURES IN PATIENTS WITH OSTEOPOROSIS. PROBLEMATIC ISSUES AND DEVELOPMENT PROSPECTS - Korzh, Mykola; Makarov, Vasyl (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Fractures of the proximal part of the humerus (FPPH) are the third most common in the elderly after fractures of the femur and radius. Objective. On the basis of analysis of the literature to identify problematic issues of surgical treatment of patients with FPPH and osteoporosis and prospects for improving implants and algorithms treatment. Methods. The material of the study was the scientific papers available in Google search engines, PubMed, Medline, published in specialized sources. Results. It is shown that are used today there are Neer and AO/OTA classifications of FPPH. Conservatively manage of FPPH in 80 % of patients with two-fragmentary fractures according to Neer or type A2/A3 according to AO/OTA. The remaining 20 % patients have threeand four-segment FPPH (types B and C according to AO/OTA), the conservative treatment of which consists of problem, especially in patients with osteopenia and osteoporosis. Surgical treatment of FPPH is recommended in case of fractures types 11B2-3, 11C2-3 in young patients or in the elderly age that requires significant functionality of the upper extremity. Positive results of treatment of FPPH types 11B3, 11C2-3 on the background of osteoporosis obtained after installation LCP-plates with allo- or autograft from the fibula bones, as well as support screws, filling of cavities in the humerus head fragments with bone cement, or using free bone implants are most often used. These methods achieve and support to enable stable repositioning of even complex type fractures 11C2-3. Blocked intramedullary nails of the third generation have improved mechanisms for attaching proximal screws and specific fixation of bone fragments, as well as straight geometry. Primary reverse shoulder arthroplasty in case of type 11С2, 11С3 fractures according to AO/OTA enables to obtain positive results in most patients. Conclusions. Surgical treatment of patients with FPPH is advisable for active patients, it is possible to improve functional results compared to conservative manage and avoid the most complications of it.